2012
DOI: 10.1590/s0102-33062012000300020
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica da comunidade arbórea em uma floresta estacional semidecidual sob queimadas recorrentes

Abstract: RESUMO(Dinâmica da comunidade arbórea em uma floresta estacional semidecidual sob queimadas recorrentes). Os efeitos do fogo sobre a mortalidade de árvores podem alterar a composição e estrutura da vegetação, dependendo da intensidade, frequência e duração das queimadas. Monitoramos áreas de floresta sujeitas a diferentes frequências de fogo no Parque Estadual da Serra Azul, Barra do Garças, MT: 0,9 ha queimaram em 2007 (Q1) e 0,9 ha em 2005 e 2007 (Q2). A dinâmica foi referente ao intervalo médio de 2,02 anos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
2
6
1
4
Order By: Relevance
“…In this study, we found a significantly higher number of species in the forest with higher frequency of burning (Peixoto et al 2012). This reinforces the differences in richness, diversity, and equitability values for the frugivorous butterfly community in the PESA phytophysiognomies, with higher values in forested areas when compared to typical Cerrado areas.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, we found a significantly higher number of species in the forest with higher frequency of burning (Peixoto et al 2012). This reinforces the differences in richness, diversity, and equitability values for the frugivorous butterfly community in the PESA phytophysiognomies, with higher values in forested areas when compared to typical Cerrado areas.…”
Section: Discussionsupporting
confidence: 86%
“…Cerrado sensu stricto and deciduous forest showed similar ecological metrics. Such pattern may be related to periodic disturbances, such as the frequency and intensity of fires (e.g., Santos et al 2017), which alter the floristic structure of the PESA physiognomies (e.g., Peixoto et al 2012 and, consequently, the organisms that depend on such physiognomies.…”
Section: Discussionmentioning
confidence: 99%
“…The S values in all three surveys were intermediate in relation to other seasonal semideciduous forest with known fire occurrences; Peixoto et al (2012) reported from 148 to 168 species, while Abreu, Pinto and Mews (2014) reported from 102 to 100 species under similar conditions, and the latter group was unable to identify alterations in the forest community after a fire event (as was seen in the present study).…”
Section: Discussioncontrasting
confidence: 74%
“…Neste sentido Ribeiro et al (2012) mostram que as constantes queimadas em áreas de cerrados oriundas de ação humana afetam a sobrevivência e o crescimento da vegetação lenhosa. Em áreas de floresta estacional semidecidual a mortalidade de árvores pode alterar a composição e estrutura da vegetação, dependendo da intensidade, frequência e duração das queimadas, assim como constatado por Peixoto et al, (2012), formações vegetais essas que estão presentes na área da bacia.…”
Section: Figura 4 -Mapa De Fragilidade Ambiental Fonte: Organização Dunclassified